2019
DOI: 10.1108/tqm-03-2019-0080
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of industry clockspeed on Lean Manufacturing implementation in Zimbabwe

Abstract: Purpose The purpose of this paper is to analyze the moderating impact of industry clockspeed (IC) on the relationship between Lean Manufacturing (LM) practices and operational performance. A model for evaluating the impact of LM is developed and the moderating effect of IC is taken into consideration as a fundamental variable that affects the causal relationship between LM practices and operational performance. Design/methodology/approach A structural equation model was proposed and investigated across two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…It must align internal resources, capabilities, and strategies with external factors, such as strategic alliances with customers and suppliers, to ensure that changes in the product mix are coherent with industry changes [ 15 , 35 ]. Thus, in line with the researchers’ suggestions, we explain the moderating role of IC on the relationship between SCI practices and NPF [ 15 , 16 ].…”
Section: Theory and Hypothesessupporting
confidence: 77%
See 2 more Smart Citations
“…It must align internal resources, capabilities, and strategies with external factors, such as strategic alliances with customers and suppliers, to ensure that changes in the product mix are coherent with industry changes [ 15 , 35 ]. Thus, in line with the researchers’ suggestions, we explain the moderating role of IC on the relationship between SCI practices and NPF [ 15 , 16 ].…”
Section: Theory and Hypothesessupporting
confidence: 77%
“…A firm develops an internal and external integrated mechanism to collect information, coordinate and monitor the partners' performance and develop a coordinated response to the customers’ needs [ 21 ]. Therefore, IC is expected to moderate the relationship between SCI practices and NPF [ 16 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted by researchers in the developed countries showed an improvement in product quality and delivery time (Papalexi et al , 2015; Nguyen and Do, 2016); productivity (Marin-Garcia and Bonavia, 2015); market share, sales, profit margins, cost, labour productivity and lead time (Chavez et al , 2015); reduction of cycle time, inventory and bottlenecks (Lacerda et al , 2016); product mix improvement (Bevilacqua et al , 2016); turnover (Bevilacqua et al , 2017) and reduction in waste and inefficiencies (Belvedere et al , 2019). The studies conducted by the researchers in the developing world also showed an improvement in operational performance variables such as profitability, sales and customer satisfaction (Nawanir et al , 2016); lead time and turnover improvement (Marodin et al , 2016); inventory reduction (Marodin et al , 2017; Panwar et al , 2017; Marodin et al , 2016); financial performance (Sahoo and Yadav, 2018); speed, flexibility and dependability (Maware and Adetunji, 2019a; Maware and Adetunji, 2019b); productivity and quality (Marodin et al , 2018; Panwar et al , 2017; El-Khalil, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…VIF was used to measure the collinearity of the latent variables and the VIF values ranged between 1 and 2.015 and were all greater than 0.2 but lower than 5 (Hair et al, 2017). If the 29 Article DOI: 10.52589/IJEBI-4BPRAF3I DOI URL: https://doi.org/10.52589/IJEBI-4BPRAF3I www.abjournals.org VIF value is lower than 5, it shows that the model has no collinearity problem (Maware & Adetunji, 2019). As such, the results showed that the AEL model had no collinearity problem.…”
Section: Model Assessmentmentioning
confidence: 93%